2017
DOI: 10.3390/app7050460
|View full text |Cite
|
Sign up to set email alerts
|

Automated Diatom Classification (Part B): A Deep Learning Approach

Abstract: Diatoms, a kind of algae microorganisms with several species, are quite useful for water quality determination, one of the hottest topics in applied biology nowadays. At the same time, deep learning and convolutional neural networks (CNN) are becoming an extensively used technique for image classification in a variety of problems. This paper approaches diatom classification with this technique, in order to demonstrate whether it is suitable for solving the classification problem. An extensive dataset was speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 11 publications
3
100
2
1
Order By: Relevance
“…While data augmentation may introduce some bias in the experiments, mainly related to the invariant features, our aim in adding the augmentation was to compare classic methods with deep learning (see [24]), for which the same augmentation is done. Moreover, as mentioned above, most features (85%) are not invariant to rotation and mirroring, and therefore, data represented with these features can be considered without bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While data augmentation may introduce some bias in the experiments, mainly related to the invariant features, our aim in adding the augmentation was to compare classic methods with deep learning (see [24]), for which the same augmentation is done. Moreover, as mentioned above, most features (85%) are not invariant to rotation and mirroring, and therefore, data represented with these features can be considered without bias.…”
Section: Resultsmentioning
confidence: 99%
“…They obtained an accuracy up to 96.3%. The other work related to CNN applied to diatoms is the one published by the authors (see the next paper companion [24]). The work presented here and the methodology have been compared to the CNN approach [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the classical method part (Dorado 2016;Pedraza et al 2017a), shape feature extraction are first done, then SVM and RF classifiers are used to classify different diatom categories. In the novel method part (Dorado 2016;Pedraza et al 2017b), a deep learning framework (CNN) is designed using the Caffe and LeNet resources. In the experiment, 80 types of the WMs (100 samples/type) are used to test the effectiveness of the methods, and the best accuracy around 99.96% is obtained using the deep learning method.…”
Section: Original Methodsmentioning
confidence: 99%
“…Existing instruments take images with a 10-20× magnification of cells. In recent studies, the differentiation of up to 80 species as maximum was demonstrated with machine learning (50). Since 2009, the ImageStream X Mk II (Luminex, Austin, Texas) IFC has been available and used mainly for biomedical research, only occasionally has it been used for phytoplankton analysis (45,46).…”
Section: Imaging Flow Cytometrymentioning
confidence: 99%